First case report of infection by Mycobacterium wolinskyi after mammoplasty in Brazil - Andrea Santos Lima; Maria Madileuza Carneiro Neves; Karen Machado Gomes; Klarissa Miranda Guarines; Carlos Feitosa Luna; Rafael Silva Duarte; Lílian Maria Lapa Montenegro; Haiana Charifker Schindler (MDPI AG, 2013)
Mycobacterium wolinskyi is a rapidly growing mycobacterium, first described in 1999 as a member of the group Mycobacterium smegmatis (Mycobacterium smegmatis, Mycobacterium wolinskyi and Mycobacterium goodii). Only 19 case reports all over the world have been described on literature, none of them in Brazil. On this report, it is described one case of infection after a mammoplasty procedure performed in a private health service in the county of Recife, Pernambuco, Brazil, in 2009. The mycobacteria specie was identified using biochemical tests and sequencing the specific gene rpoB. To treat the infection by Mycobacterium wolinskyi it was necessary to combine antibiotics for a long period of time associated with surgical procedures of the breast abscesses.